2021
DOI: 10.3390/endocrines2040044
|View full text |Cite
|
Sign up to set email alerts
|

Stress Axis in the Cancer Patient: Clinical Aspects and Management

Abstract: Hypothalamus–pituitary–adrenal (HPA) axis alterations are common in cancer patients, mainly due to the different antitumoral therapies, which lead to several acute and late endocrine side effects. This review summarizes the most recent evidence regarding HPA derangement, both in patients with active neoplasms and in cancer survivors, with particular attention to the impact of the different antitumoral treatments, focusing on the major clinical aspects. While acute hormone failure usually results from injury ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…A role of inflammation has been widely studied in many aspects of cancer development including initiation, promotion, and progression, and both positive and negative correlation between inflammation and cancer have been reported ( Liu et al, 2021 ), Conversely, cancer itself alters the balance of cytokine production toward an inflammatory milieu ( Burkholder et al, 2014 ). Apart from cancer itself, a persistent proinflammatory state in cancer patients is often the result of either targeted therapy or palliative treatment ( Ahmad et al, 2021 ; Francesco et al, 2021 ). Regardless of their origin, the pro-inflammatory cytokines produced in the periphery can enter the circulation, permeate the blood-brain barrier, increase the production of local inflammatory mediators, and subsequently impair stress responses ( Figure 1 ).…”
Section: Chronic Stress and Cancer—a Bidirectional Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…A role of inflammation has been widely studied in many aspects of cancer development including initiation, promotion, and progression, and both positive and negative correlation between inflammation and cancer have been reported ( Liu et al, 2021 ), Conversely, cancer itself alters the balance of cytokine production toward an inflammatory milieu ( Burkholder et al, 2014 ). Apart from cancer itself, a persistent proinflammatory state in cancer patients is often the result of either targeted therapy or palliative treatment ( Ahmad et al, 2021 ; Francesco et al, 2021 ). Regardless of their origin, the pro-inflammatory cytokines produced in the periphery can enter the circulation, permeate the blood-brain barrier, increase the production of local inflammatory mediators, and subsequently impair stress responses ( Figure 1 ).…”
Section: Chronic Stress and Cancer—a Bidirectional Relationshipmentioning
confidence: 99%
“…Clinical data strongly indicate a dysregulated HPA axis function and abnormal secretion of cortisol in cancer patients ( Weinrib et al, 2010 ). In these patients, cortisol levels can be altered due to several factors including the cancer itself, treatments such as chemotherapy, and psychological stress associated with a cancer diagnosis ( Francesco et al, 2021 ). Thus, an altered cortisol diurnal rhythm has been demonstrated in patients with cancer prior to surgery ( Schrepf et al, 2015 ; Chang and Lin, 2017 ), and an aberrant nocturnal cortisol has been shown in women with advanced breast cancer ( Zeitzer et al, 2016 ).…”
Section: Chronic Stress and Cancer—a Bidirectional Relationshipmentioning
confidence: 99%
“…This concept, known as tumor dormancy, is believed to arise from an immunologic equilibrium between the host and the tumor [28,29]. The hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system (SNS) regulate immune responses, both of which are activated by surgery and general anesthesia [30,31] (Fig. 2).…”
Section: Role Of Anesthesia In Immune System Modulationmentioning
confidence: 99%
“…While there is no accepted mechanistic model explaining the reduction in CRF induced by exercise, it would be possible to provide such a theoretical model by using available evidence from exercise studies performed with cancer patients, or other chronic diseases like chronic fatigue syndrome [ 22 ], as well as healthy patients. In fact, among the suggested mechanisms involved in CRF etiology, some of them may be acutely influenced by aerobic exercise, such as peripheral pro-inflammatory state [ 23 ], immune function dysregulation [ 14 , 24 ], as well as neuroendocrine dysregulations [ 25 , 26 ]. Hence, the objective of this conceptual review is to provide a theoretical model explaining how aerobic exercise may reduce CRF.…”
Section: Introductionmentioning
confidence: 99%